Review: The Messiah in Isaiah 53: The Commentaries of Saadia Gaon, Salmon ben Yeruham, and Yefet ben Eli on Is. 52:13–53:12 - Polliack, Meira (The journal of theological studies, 2005)
The Messiah in Isaiah 53: The Commentaries of Saadia Gaon, Salmon ben Yeruham, and Yefet ben Eli on Is. 52:13–53:12 Edition and translation by Joseph Alobaidi 211 (La Bible dans l’histoire.)Bern Peter Lang 1998 3 906760 54 5 Paper£19